First record of Monalonion velezangeli (Hemiptera: Miridae) affecting avocado and cherimoya (Annona cherimola) as new hosts in Ecuador - Noboa, Michelle; Castillo, Carmen; Carvajal, Vladimir; Merino, Jorge; Gaona, Pablo; Viteri, Pablo; Park, Chan Hwan (Zootaxa, 2024)
Monalonion velezangeli is a polyphagous hemipteran reported as one of the main pests of economic importance in avocado and coffee crops. This is the first report of M. velezangeli affecting avocado (Persea americana (Mill)) in Ecuador and the first report of cherimoya (Annona cherimola) as a new host plant. The species was identified through classical taxonomy based on morphology, with parallel molecular identification targeting the cytochrome oxidase I region.